Prototype of automatic weighing scale for a corn sheller using information technologies - Aspiazu-Sevillano, Nathaly; Perez-Espinoza, Charles; Samaniego-Cobo, Teresa (International Journal of Computational Innovations, Intelligent Systems and AI, 2026)
The study describes the design and evaluation of a prototype automatic scale integrated into a corn sheller, aimed at improving the efficiency and control of post-harvest processes through the use of information technologies. The prototype was evaluated through expert validation, considering indicators of operational efficiency, technological integration, accuracy, and reliability, as well as feasibility and scalability. The results show moderate-favorable overall acceptance (58.33%), with the feasibility and scalability indicator receiving the highest rating (65.33%), reflecting recognition of the implementation potential of the proposed solution. However, the experts identified critical areas for improvement related to metrological accuracy and systemic integration, which are typical of technologies in the early stages of development. Overall, the findings suggest that the prototype is a technologically relevant alternative for the modernization of post-harvest processes in the agricultural sector. Likewise, the future incorporation of artificial intelligence techniques is proposed as a way to improve the system's performance and strengthen its scalability in precision agriculture environments.